LINGUOCULTURAL ANALYSIS OF PHRASEOLOGICAL UNITS WITH ONOMASTIC COMPONENTS IN ENGLISH AND RUSSIAN LANGUAGES - Radjabova Marjona Akhmadovna (Modern American Journals, 2025)
In this article the author analyses national identity and national-cultural aspects of phraseological units with onomastic component in unrelated English and Russian languages. The linguocultural study of onomastic units in phraseological units allows us to get acquainted with the centuries-old history of the English and Russian peoples, as well as with their national values.
Keywords: Nomastic unity, phraseological unity, linguocultural analysis, culture, national identity, component.